2015
DOI: 10.1016/j.vaccine.2015.09.057
|View full text |Cite
|
Sign up to set email alerts
|

Whole organism blood stage vaccines against malaria

Abstract: Despite a century of research focused on the development and implementation of effective control strategies, infection with the malaria parasite continues to result in significant morbidity and mortality worldwide. An effective malaria vaccine is considered by many to be the definitive solution. Yet, after decades of research, we are still without a vaccine that is capable of inducing robust, long lasting protection in naturally exposed individuals. Extensive sub-unit vaccine development focused on the blood s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 46 publications
1
20
0
Order By: Relevance
“…Although whole‐organism malaria vaccine has regained attention recently, there are still many challenges to use them in humans, including the blood transfusion adverse reactions and high dose of immunogen. Studies have indicated that the whole‐organism malaria vaccines, which will incorporate the human erythrocytes in the final vaccine products, may result in the induction of antibodies against red blood cell surface antigens (eg ABO and Rh blood group systems) . More solutions to address the blood transfusion reactions of whole‐organism malaria vaccine should be proposed in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although whole‐organism malaria vaccine has regained attention recently, there are still many challenges to use them in humans, including the blood transfusion adverse reactions and high dose of immunogen. Studies have indicated that the whole‐organism malaria vaccines, which will incorporate the human erythrocytes in the final vaccine products, may result in the induction of antibodies against red blood cell surface antigens (eg ABO and Rh blood group systems) . More solutions to address the blood transfusion reactions of whole‐organism malaria vaccine should be proposed in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have indicated that the whole-organism malaria vaccines, which will incorporate the human erythrocytes in the final vaccine products, may result in the induction of antibodies against red blood cell surface antigens (eg ABO and Rh blood group systems). 39,40 More solutions to address the blood transfusion reactions of whole-organism malaria vaccine should be proposed in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, both malaria parasite-specific IgG and MCP-1 in immunized serum are responsible for the suppression of parasite development in mosquitoes. Due to the failure of subunit malaria vaccines against the blood stage, whole-organism vaccines have received much attention in recent years and have been demonstrated to induce protective immunity against the blood stage (22). Vaccines against the blood stage reduce the morbidity and mortality of malaria patients; however, whether these vaccines also inhibit the development of malaria parasites in mosquitoes remains unknown.…”
Section: Mcp-1 and Parasite-specific Igg In Wkv-immunized Serum Inhibmentioning
confidence: 99%
“…Given that parasites are likely to develop resistance to newly introduced drugs, alternative strategies are required to treat malaria infections. Mass vaccination would be a better strategy, but an effective vaccine is not available, and its development remains challenging (8,9). Gaining insight into the molecular and cellular processes involved in protective immunity and pathogenesis may help in the design of an efficacious vaccine and/or immunomodulation agents to treat malaria (10,11).…”
mentioning
confidence: 99%